Kaurna warrapiipa Kaurna dictionary : Kaurna to English, English to Kaurna - Amery, Rob 1954- (Kaurna Warra Pintyanthi in association with Wakefield Press, 2021)
Kaurna to English and English to Kaurna translations give learners quick access and the ability to identify the creative processes used to translate and adapt old words to new for modern day application that is rooted in ancient integrity. This simple, comprehensive and insightful dictionary is easy to navigate and is grounded with ancient and modern Kaurna voices and robust historical and contemporary sources. -- Back cover of print version